Depiction of Agni on the Kakshasana of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Agni, the deity of the southeast direction, is also portrayed on the kakshasana (seat back) of the Undeshwar Temple. He holds a pointed spoon and a flower in his upper hands. Unfortunately, his lower hands are damaged, as is the face of his vehicle. Agni is adorned with a jatamukuta (crown of matted hair) and has a beard.